Ricinus communis, Castor Bean - Melissa H. Friedman; Michael G. Andreu; Heather V. Quintana; Mary McKenzie (EDIS)
This document provides an overview of the castor bean plant (Ricinus communis), detailing its characteristics, uses, and potential hazards. It describes the plant’s growth habits, physical features, and its classification as an invasive species in Florida. The article also highlights the plant’s allergenic properties and the toxicity of its seeds, which contain ricin. Additionally, it outlines the commercial, horticultural, and medicinal applications of castor oil derived from the seeds, emphasizing the importance of careful handling due to the plant’s toxic nature. Original publication date May 2010.